PERBANDINGAN PERTUMBUHAN RUMPUT PAKCHONG (Pennisetum purpureum cv. Thailand) PENGARUH PEMBERIAN BEBERAPA POC DAN KETINGGIAN POTONG PERTAMA - Sembiring, Anggi Calfin; Meriksa Sembiring (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine the effect of liquid organic fertilizer (POC) and the height of the first cutting and the interaction on the growth and fresh weight of pakchong grass (Pennisetum purpureum cv Thailand L.), as well as to determine the effect of different first cutting heights on the growth and fresh weight of pakchong grass (Pennisetum Purpureum cv Thailand L). The design is to use a factorial Randomized Group Design (RAK) consisting of 2 factors, namely the first factor consists of 2 levels, namely T1 (one internode) and T2 (2 internodes), the second factor consists of 3 levels, namely P0 (control), P1 (POC Hantu), P2 (POC Vio), with 6 treatment combinations and 4 replicates. Fertilization using POC at a dose of 0.5% sprayed on plants at 2, 3 and 4 weeks after planting (mst). The observation parameters were height growth, stem diameter, number of tillers and fresh and dry forage production. Observations for grass height at 2, 4, and 6 mst, while for the number of tillers and stem diameter were done before harvest (40 hst) and fresh forage production was done at harvest. Data were analyzed statistically, if in the test there is a real difference then it will be continued with testing using DMRT. The results of the research on the parameters observed from the effect of some POC usage with the results of the effect of cutting length differed not significantly (p>0.05) to the diameter and number of tillers, significantly different (p<0.05) to production. The highest results of using POC Hantu (P1) for fresh weight and dry weight. There is no interaction but the best wet and dry weight production is P2T1.